(untitled) (Global Journal of Management and Business Research, 2013)
In this paper we approach as to whether CEO#x2019;s incentives may lead to a positive manager#x2019;s innovation behavior. We search in this work to study this relationship conforming to the prediction of the theory of commitment. Accordingly, we hypothesize that CEO#x2019;s incentives can persuade a favorable attitude toward innovation but it can lead to an authentic behavior only with the presence of commitment bias. The proposed model of this paper uses Bayesian Network Method to examine this relationship. CEO#x2019;s attitude has been measured by means of a questionnaire comprising several items. As for the selected sample, it has been composed of some 220 Tunisian executives. Our results have revealed the efficient role of governance mechanism as a persuasive communication on the CEO#x2019;s attitude; however, only managers who note a high commitment level behave authentically to their attitude and decide R